Experimental response and fiber‐reinforced cement composites strengthening of real reinforced concrete columns with poor‐quality concrete. (7th January 2019) - Del Vecchio, Ciro; Di Ludovico, Marco; Balsamo, Alberto; Prota, Andrea; Cosenza, Edoardo
Abstract : Poor‐quality concrete and a lack of transverse reinforcement commonly characterize the reinforced concrete (RC) structures built during the past century in the Mediterranean area. However, very few experiments have investigated the performance of structural members of that kind. Moreover, the design of repair and retrofit solutions using available techniques could be challenging due to the weakness of the concrete substrate. This paper reports on the experimental response and the repair and retrofit of existing RC columns with poor‐quality concrete. In particular, it presents and discusses the outcomes of three tests on two RC columns extracted from a real building that was severely damaged by the 2009 L'Aquila earthquake and was, as a result, demolished. The concrete compressive strengths resulting from in situ and laboratory material characterization tests are used to predict the axial strength of the sampled columns. An innovative application of fiber‐reinforced cement composites (FRCC) for the repair and retrofit of damaged columns is proposed and validated experimentally. The results reveal that this material is effective when it comes to recovering and improving the axial capacity of damaged RC members. Practical suggestions to account for the confinement effect of the thin FRCC jacketing in available analytical formulations are discussed.